2014
DOI: 10.2478/amm-2014-0052
|View full text |Cite
|
Sign up to set email alerts
|

Producing Ultrafine Grain Structure in AZ91 Magnesium Alloy Cast by Rapid Solidification

Abstract: The paper presents the technological aspect of the process of casting, crushing and plastic consolidation of semi-finished products from magnesium alloy. The aim of this study was to produce by the rapid solidification process a magnesium alloy from the MgAl9Zn1 family in the form of ribbons with ultrafine grain structure. The material cast in the melt spinning device was next crushed and subjected to the operation of cold consolidation and hot extrusion. The paper presents different stages of the process, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The DCP is a fundamental characteristic of as-cast alloys, because it indicates the transition from mass to interdendritic feeding during crystallisation [1,4,7]. Casting defects, such as macrosegregation, shrinkage, porosity and hot tearing begins below the DCP [4,[8][9][10]. Consequently, a thorough , T. Tański*, G. MaTula*, P. snoPiński*, a.E.…”
Section: Introductionmentioning
confidence: 99%
“…The DCP is a fundamental characteristic of as-cast alloys, because it indicates the transition from mass to interdendritic feeding during crystallisation [1,4,7]. Casting defects, such as macrosegregation, shrinkage, porosity and hot tearing begins below the DCP [4,[8][9][10]. Consequently, a thorough , T. Tański*, G. MaTula*, P. snoPiński*, a.E.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain massive materials from small-sized ribbons (thickness 50-200 μm and width 2-30 mm) it is necessary to apply consolidation processes, i.e. pressing and hot extrusion or forging [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have clearly demonstrated that the nanostructuring of metallic biomaterials can considerably improve not only its mechanical properties but also the biocompatibility [6]. The nanocrystalline structures can be produced by non-equilibrium processing technique such as mechanical alloying (MA) [7] or rapid solidification [8].…”
Section: Introductionmentioning
confidence: 99%